2022
DOI: 10.1038/s41598-022-18529-6
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral prefrontal cortex plays causal role in probability weighting during risky choice

Abstract: In this study, we provide causal evidence that the dorsolateral prefrontal cortex (DLPFC) supports the computation of subjective value in choices under risk via its involvement in probability weighting. Following offline continuous theta-burst transcranial magnetic stimulation (cTBS) of the DLPFC subjects (N = 30, mean age 23.6, 56% females) completed a computerized task consisting of 96 binary lottery choice questions presented in random order. Using the hierarchical Bayesian modeling approach, we then estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…At first glance, these studies seem at odds with our observation. However, the effect of cTBS in risk-taking behavior and increasing dopamine release seems to be limited to the left DLPFC (and not the right DLPFC) [Ko et al, 2008, Ott et al, 2011, Panidi et al, 2022]. A recent meta-analysis of fMRI studies related to exploration-exploitation-related tasks (e.g., armed bandit and foraging tasks) showed that rDLPFC activation is specific for exploration and not risk [Zhen et al, 2022].…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, these studies seem at odds with our observation. However, the effect of cTBS in risk-taking behavior and increasing dopamine release seems to be limited to the left DLPFC (and not the right DLPFC) [Ko et al, 2008, Ott et al, 2011, Panidi et al, 2022]. A recent meta-analysis of fMRI studies related to exploration-exploitation-related tasks (e.g., armed bandit and foraging tasks) showed that rDLPFC activation is specific for exploration and not risk [Zhen et al, 2022].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol closely follows the one used in a previous TMS study on the role of the DLPFC in risky choice (Panidi et al, 2022). The experimental task consisted of 85 selfpaced binary lottery choice questions.…”
Section: Experimental Task and Paymentmentioning
confidence: 99%
“…According to the results of invasive animal studies, a number of areas critical for movement preparation and execution are also encoding MDM parameters. 10,52-55 Recently it has been suggested that prefrontal cortical areas such as DLPFC, responsible for goal valuation during decision-making under risk, 56 also modulates motor output, speeding up movement execution. 57 Some evidence suggests the orbitofrontal cortex involvement in encoding values for the movements’ endpoints.…”
Section: Neurophysiological Basis Of Neuroeconomics Approach To Motor...mentioning
confidence: 99%